2011
DOI: 10.1108/09565691111152062
|View full text |Cite
|
Sign up to set email alerts
|

ICT and digital records management in the Ugandan public service

Abstract: PurposeThe purpose of this paper is to present empirical research findings regarding the contribution of Information and Communication Technology (ICT), such as computers, to creating and managing digital records in the Ugandan Public Service (UPS). It seeks to review the ICT developments in Uganda and to discuss the extent to which UPS agencies have adopted digital record‐keeping systems, how the management of digital records is incorporated with ICT strategies, and to identify challenges faced.Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Matangira (2016) argues that top management in Zimbabwe’s public service did not prioritise records management activities, which they usually accorded a low profile. Similar sentiments were raised by Luyombya (2010) in Uganda who holds that public sector management usually saw the importance of records and records management only when things went wrong or when an important file could not be located.…”
Section: Data Analysis and Discussionmentioning
confidence: 56%
“…Matangira (2016) argues that top management in Zimbabwe’s public service did not prioritise records management activities, which they usually accorded a low profile. Similar sentiments were raised by Luyombya (2010) in Uganda who holds that public sector management usually saw the importance of records and records management only when things went wrong or when an important file could not be located.…”
Section: Data Analysis and Discussionmentioning
confidence: 56%
“…In Uganda, commenting upon the rather negative attitude of senior management, Luyombya (2010) states that the value of records was only seen by senior managers when an important record went missing. A study by Majenda and Dewah (2019) on missing records at a public sector organisation in Zimbabwe revealed that senior managers normally did not assist junior records officers in fighting the missing records scourge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The RAM studies were undertaken in Botswana (Mampe and Kalusopa, 2012) and South Africa (Kanzi, 2010; Marutha, 2013). In East Africa, studies were carried in Kenya (Chimwani, Iravo, and Tirimba, 2014; Kendo and Getuno, 2016), Uganda (Luyombya, 2010; Namukasa, 2017), Ghana (Tagbotor, et al , 2015) and Tanzania (Kitalu, 2001; Ndibalema, 2001; Chachage, 2005; Lyaruu, 2005; Ndenje-Sichalwe, 2010; Ndemanyisho, 2014). Most of these empirical studies were either in successes or failures of the RAM practices.…”
Section: Selected Empirical Literature On Records and Archives Managementmentioning
confidence: 99%